Revised purchase order for electrical cables for HAVC works for BRACU new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Poly Cables Ind. Ltd. for the supply of electrical cables for HVAC work for Brac University new campus project.